VD_FINDINFO Jug / 2015 / 344 vom 12. Mai 2015 - VD Tribunal cantonal (2015)
FRAISEN GÉNÉRAL, INDEMNITÉEN GÉNÉRAL, REJET DE LA DEMANDE | 398 al. 1 CPP (CH), 426 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH), 430 al. 1 let. a CPP (CH)